Letter from Louis Pasteur to an unidentified colleague, 1891 - Pasteur, Louis (1891)
In this letter Louis Pasteur addresses a "very eminent colleague," and thanks him for an advance copy of a new work on social economy.
Keywords: Microbiologists; Chemists; Pasteur, Louis, 1822-1895; Turgot, Anne-Robert-Jacques, baron de l'Aulne, 1727-1781